Just and lasting change : When communities own their futures - Taylor, Daniel C. (Johns Hopkins University Press, 2002)
Just and Lasting Change presents how to transform communities rapidly and inlocally appropriate ways. Daniel Taylor-Ide and Carl Taylor have been present at key events and worked with key thinkers in dealing with the large forces of inequity, environmental change, and globalization. The approach they have synthesized builds on what has worked over the last century-and can now be implemented rapidly and cost-effectively in many parts of the world.